Educated Spoken Arabic in Algerian Radio: A French- Arabic Linguistic Fusion - Horiya Amar Bekada; Mohammed Messahel (International Journal of Social Communication, 2025)
In a society where both formal Arabic (Modern Standard Arabic) and informal Arabic (Algerian Arabic) coexist, radio presenters in Algeria navigate a complex linguistic landscape. This paper investigates a distinctive linguistic blend known as Educated Spoken Arabic (ESA), which merges features of formal Arabic and French. ESA serves as a communicative bridge between formal and informal registers, offering a dynamic and accessible mode of communication. Drawing on audio recordings from Ain Temouchent local radio station, this study explores the historical emergence of ESA, identifies its key linguistic features, and assesses its broader impact on the Arabic linguistic environment. The findings indicate that ESA is a flexible, evolving linguistic hybrid that reflects the unique identity of Algerian radio broadcasting.